Age and gender differences in prevalence of screen based behaviour, physical activity and health complaints among Slovak school-aged children - Husárová, Daniela; Veselská, Zuzana; Sigmundová, Dagmar; Gecková, Andrea (Central European Journal of Public Health, 2015)
AIM: The aim of this study was to assess age and gender differences in prevalence of screen based behaviour, physical activity and health complaints among Slovak school-aged children. METHODS: Data from the cross-sectional Health Behaviour of School-aged Children study collected in 2010 among Slovak children (age 11-15 years, N=8,042) was used. Logistic regression models adjusted to age and gender were used to analyse the associations between watching TV, working with a computer or playing computer games and physical activity and headache, backache, sleep difficulties, feeling low, irritability, and feeling nervous. RESULTS: Around one-quarter of adolescents is spending more than three hours a day with screen-based activities. While the age was significantly associated with watching TV and computer use, gender was significantly associated only with excessive computer use. As for physical activity only 25% of adolescents reported being physically active every day as recommended, and this number decreases with increasing age. Boys used to be more often active in comparison with girls. A sizeable number of adolescents suffer with selected health complaints every week. Moreover, the prevalence of health complaints increases with age and is significantly higher among girls. CONCLUSIONS: The prevalence of screen-based activities as well as insufficient physical activity and health complaints among adolescents is relatively high and it increases with age. Gender differences are also significant, except for watching TV.
Keywords: Sedentary Behavior; průzkumy a dotazníky; Female; Prevalence; dítě; Television; Age Factors; Health Status Indicators; ženské pohlaví; sedavý životní styl; Surveys and Questionnaires; Adolescent Behavior; Adolescent; pohybová aktivita; Slovakia; věkové faktory; lidé; ukazatele zdravotního stavu; Computers; Humans; Sex Factors; prevalence; Male; sexuální faktory; televize; mladiství; videohry; Video Games; Motor Activity; Child; Slovenská republika; počítače; mužské pohlaví; chování mladistvých; chování dětí; Child Behavior